Detection of canine distemper virus in wildlife in Italy (2022–2024) - Alfano, Flora; Lucibelli, Maria Gabriella; D’Alessio, Nicola; Auriemma, Clementina; Rea, Simona; Sgroi, Giovanni; Lucente, Maria Stella; Pellegrini, Francesco; Diakoudi, Georgia; De Carlo, Esterina; Decaro, Nicola; Lanave, Gianvito; et al. (Frontiers in Veterinary Science, 2025)
CDV has been detected in a wide range of domestic and wild animal also in Italy and it is highly prone to cross-species transmission, therefore representing a significant health risk. In this study the presence of CDV and other coinfecting selected viruses, in wild carnivorans of the family Mustelidae and Canidae and rodents of the family Hystricidae, collected in Southern Italy (Campania region), in 2022–2024, was investigated. Over a period of 3 years (2022–2024), tissue samples from 136 wild animals including stone martens, porcupines, otters, wolves, martens, badgers and foxes were examined. CDV RNA was detected in 14 (10.3%) animals encompassing badgers (n = 6), foxes (n = 5), wolves (n = 2), and marten (n = 1). The complete genome of a CDV strain was reconstructed from a spleen sample of a badger. On sequence and phylogenetic analyses, the novel CDV strain belonged to the Arctic clade, which has already been reported from badger and dog in Italy. Our study contributes to extend the knowledge on the epidemiology of CDV in wildlife and confirm the need for a continuous surveillance in wild animals to monitor the circulation in wildlife of viruses pathogenic for domestic carnivores and endangered wild species.